Laut dan Islam: Perkembangan Kesultanan Perlak pada Abad XV - Athallah Abel Gibrani Henarwanto (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta, 2022)
Discussions about when Islam came to Nusantara are exciting topics. Although many books and journal articles have been written on this theme, many experts and other authors are still driven to review the theme again. Among the many works that write about this is a collection of writings about the introduction of Islam in Indonesia edited by A. Hasjmy, which explains the growth of the Perlak Kingdom. This writing attempts to look back at the discussion of the Perlak Kingdom contained in A. Hasjmy's book. The author thoroughly read this book before critically examining some of the information considered worthy of being discussed again. The author adds many analyses of these findings so that what emerges is an alternative view on the theme of Islamization in Indonesia. The author attempts to discuss some of the endemic findings in this writing. It cannot be denied that this book has significantly contributed to the history of Islamization in Indonesia, with various variations and developments. Some authors in this book have different backgrounds of expertise, ranging from history, sociology, anthropology, and archaeology. Indirectly, this book opens the birth of the social history perspective of Islam typologically different from other regions in the world.Artikel ini membahas bagaimana Sarekat Islam (SI) menjadi representasi dari gerakan sosial rakyat pribumi di Hindia Belanda. Penelitian ini mengunakan metode sejarah dengan pendekatan sosiologi. Lebih lanjut penelitian ini menggunakan teori mobilisasi sumber daya dalam gerakan sosial untuk melihat perkembangan pola pemikiran dan gerakan di SI. Hasil Penelitian ini menunjukkan bahwa pada awalnya, bagi rakyat pribumi SI dianggap sebagai wujud dari gerakan Ratu Adil dimana para pemimpinnya dianggap memiliki kharismatik yang akan memimpin mereka agar lepas dari kesengsaraan hidup. Namun anggapan ini kemudian berubah, bukan hanya karena para pemimpin SI menolak anggapan Ratu Adil itu, namun juga karena di dalam Sarekat Islam sendiri mulai berkembang sebuah pemikiran yang lebih rasional dan modern yakni sosialisme serta reformisme Islam dalam merespon kondisi di Hindia Belanda, yang akhirnya mewujudkan perkembangan ideologi dan gerakan di dalam SI. Paham sosialisme-marxisme (komunisme) yang bertentangan dasar dengan Islam membuat SI akhirnya terpecah-belah. Banyak konflik terjadi antara kubu yang menganut komunisme dengan kubu yang anti komunisme. Puncaknya yakni ketika SI mulai secara tegas membersihkan diri dari unsur komunisme melalui disiplin partai pada 1921.